A comparative study of vaginal delivery and caesarean section in antepartum eclampsia at and beyond 34 weeks of gestation - Srujana, A.; Jyothi, C.; Swathi, K.; Sharmila, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was done to compare maternal and fetal outcome in pregnancies after 34 weeks gestation complicated by antepartum eclampsia when terminated by caesarean section and by vaginal delivery. Methods: A comparative prospective study was done on 100 pregnant women with antepartum eclampsia at or beyond 34 weeks of gestational age from November 2019 to June 2021 at Gandhi Hospital, Secunderabad, Telangana. The patients were divided into two groups: CD group (who delivered by caesarean section) and VD group (who delivered by vaginal route). After history taking and examination, delivery was planned according to the gestational age, foetal condition and Bishop’s score. The associated indication for caesarean, induction delivery interval in vaginal deliveries, total blood loss was noted. Baby details were noted and were followed till discharge at hospital. Results: The incidence of caesarean section was 41% and that of vaginal delivery was 59%. Highest incidence of antepartum eclampsia was seen in the age group of 20-24 years and between 37-40 weeks. Most common indication of caesarean section was fetal distress (19%). The convulsion-delivery interval was less in CD group and it was statistically significant (p value 0.01). The incidence of live births, still births and IUD was better in the CD group than VD group (p value 0.02). Perinatal mortality was more in vaginal delivery group (27.64%) than in caesarean section group (12.19%). Maternal mortality was 1.7% in the VD group and nil in the CD group. Conclusions: The study reflected that both perinatal and maternal morbidity and mortality were found to be lesser in the CD group in comparison with the VD group. Thus, early decision for caesarean section especially when delivery is not anticipated within 6 hours of admission is essential in improving the perinatal and maternal outcome in eclampsia.